The Effects of Increased Copyright Protection: An Analytic Approach - Novos, Ian E.; Waldman, Michael (Journal of Political Economy, 1984)
Previous authors who have considered partially nonexcludable goods have claimed that an increase in copyright protection will have the following two effects on social welfare. First, it will decrease the social welfare loss due to underproduction. Second, it will increase the social welfare loss due to underutilization. In this paper we investigate these claims in a formal setting by analyzing a model in which consumers vary only in terms of their costs of obtaining a reproduction. Our analysis provides partial support to the first claim of these previous authors while giving little or no support to the second claim.